Shipping Income Tariff Model Using System Dynamics Method - Dewi, Nurlaela Kumala; Adriant, Irayanti; Cristian, Ferry; Prasetyo, Wahyudi Adi (Yayasan Sinergi Kawula Muda, 2025)
The Bandung City Hub Branch expedition service company is currently facing a decrease in the number of shipments and weight of goods sent for the Jakarta - Bandung shipping route, which automatically affects the income received. This decline phenomenon can undoubtedly impact the company's financial condition and profitability. This study aims to create and simulate tariff scenarios with a system dynamics model. The scenarios created are adjusted to existing conditions and scenarios based on consumer demand. The results of the existing scenario obtained an average amount of income in the ten iterations of the existing model output of Rp 293,789,065.095 with an average profit of Rp 77,397,734.026. In the scenario based on consumer demand, the average amount of income in the ten iterations of the first scenario model output was Rp 277,636,482.287, with an average profit of Rp 61,245,151.218. These results show that the existing model conditions are still better at providing income, so the company can still use them. This model allows companies to understand the interactions of various elements of the company's business because it models cause-and-effect relationships, and companies can analyze factors such as cash flow, costs, and revenues that influence each other and help companies make long-term decisions.